Seasonal selection of key resources by cattle in a mixed savannah-wetland ecosystem increases the potential for conflict with lions. (September 2019) - Weise, Florian J.; Fynn, Richard W.S.; Stein, Andrew B.; Tomeletso, Mathata; Somers, Michael J.; Périquet, Stéphanie
Abstract: In Africa's pastoral conservation landscapes, apex predators frequently kill livestock. Retaliatory persecution such as poisoning threatens predators, but also non-target biota. Several factors influence conflict severity, including livestock husbandry, overlap in seasonal habitat use, and the degree to which livestock perceive and are able to respond to a landscape of fear. We investigated these factors by GPS-tracking 42 Tswana beef cattle ( Bos taurus ) from 29 herds in 2017 and six lions ( Panthera leo ) from different prides (May 2016–Dec. 2017) in the northern Okavango Delta, Botswana, where cattle depredation significantly impacts the livelihoods of rural agro-pastoralists. Cattle exhibited seasonal habitat selection patterns similar to wild ungulates in the region. They preferred woodland habitats, with more digestible grasses, during the wet season. During the dry season, they preferred wetland habitats with reliable forage and water availability. Cattle also preferred areas close to human settlements, but the necessity to forage in wetlands during the dry season exposed them to significant depredation risk, especially >4 km from settlements. Lions killed most cattle in wetlands during the late dry season but the intensity of recent lion presence (previous 14 days) only had a weak negative effect on cattle habitat selection patterns. Cattle used rangelands according to nutritional requirements, irrelevant of the associated predation risk, suggesting that socio-ecologically acceptable conflict solutions cannot rely on the exclusion of livestock from seasonal wetlands. Curbing depredation by lions will best be achieved by a combination of resource- and predation-cognisant seasonal herding strategies with adequate livestock protection. Understanding the ecological constraints that intensify conflict is pertinent to any livestock production landscape with predator presence. It is also a central prerequisite for future land use planning and devolution of legal, controlled resource access rights through policy. Coexistence strategies must account for the strong reliance of people, their livestock, and wildlife on shared key resources. This is particularly important in large trans-frontier conservation areas where the successful merging of biodiversity conservation and rural development is a strategic goal. Omission will foster resentment and resistance to coexistence with apex predators, particularly if livestock productivity and human livelihoods are negatively affected.